Genetic structure and designing a preliminary core collection of Zizania latifolia in China based on 12 microsatellites markers - Lei, Xiangliang; Su, Xiaona; Zhou, Chengchuan; Jiang, Shaolin; Yuan, Xiaoquan; Zhao, Yao; Jiang, Shaomei (PeerJ, 2025)
The genetic diversity and structure of wild crop relatives are crucial for their conservation and utilization in breeding programs. This study presents a comprehensive survey and collection of Zizania latifolia across its natural distribution range in China. Using 12 microsatellite markers, the genetic diversity of 357 wild Z. latifolia accessions from 25 populations was evaluated, revealing a high genetic diversity (He = 0.439). The genetic structure analysis indicated significant genetic differentiation among populations, with evidence of isolation by distance. CoreHunter3 and PowerMarker software were employed to design a preliminary core collection, and the final core collection comprised 92 wild accessions. The core collection was found to be representative of the original germplasm, ensuring the effective conservation of Z. latifolia’s genetic resources. This study would provide valuable insights for the development of conservation strategies and the utilization of Z. latifolia.
Keywords: Zizania latifolia; Microsatellites markers; Genetic diversity; Natural distribution; Germplasm